Habermas, Human Agency, and Human Genetic Enhancement: The Grown, the Made, and Responsibility for Actions - Herissone-Kelly, Peter (Cambridge quarterly of healthcare ethics, 2012)
Recent developments in genomic science hold out the tantalizing prospect of soon being able to treat and prevent a wide variety of medical conditions through gene therapy. In time, it may be possible to use similar techniques not simply to combat disease but also to enhance, or improve on, normal human functioning.